R-álgebras de dimensão finita - Oliveira, Sóstenes Souza de (2017)
In this work we study the notion of R-algebra. Roughly, they are structures that generalize some arithmetic properties of the body of complex numbers. The ?exibi- lity in this generalization is the non-requirement of properties such as commutativity, associativity and identity element existence. We focus primarily on the ?nite dimen- sional division R-algebras. As is well known, modulo isomorphisms exist exactly four of those R-algebras. In the development of the dissertation we will discuss in detail its main algebraic and geometric properties.